KEPEMIMPINAN GURU PEREMPUAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 SIPIROK KABUPATEN TAPANULI SELATAN - Yetti Sarina Siregar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
This study was to determine the leadership of female teachers, namely the exemplary behavior and interpersonal communication. The research used a qualitative method by using interviews, observation and documentation. The results inform several things, first, the female teacher's exemplary behavior shows good behavior such as a friendly, polite, neat personality, and discipline in her duties. Second, her communication behavior goes well, closely intertwined, so the material presented is easily understood. Third, her rewarding behavior in hands-on and praise sentences, rewards give influence on increasingly brave, passionate and more active. Fourth, the punishment in the form of reprimands, advice, and warnings.